Sistem Pakar Meindentifikasi Cacat Pada Rotan Tabu-Tabu - Arif Rahman Hakim; Rahmat Fauzi (Prosiding, 2018)
Taboo rattan is a large rattan with thinner and cream colored skin, and its contents (heart) are white and have rather larger pores, making rattan taboo is softer and more flexible, rattan taboos are widely used for furniture as raw material, each stem from taboos and taboos has a flaw, where every defect of the rattan affects the quality and price of the stem from a rattan taboo, so there are still many of the taboo taboo enthusiasts who do not know about defects. Sometimes people are often deceived into buying taboo taboos. Expert System is a branch of AI (Artificial Intelligence) which makes special extensions to the specialization of knowledge in order to solve a problem in the Human Expert. The method used is the backward chaining method that is suitable in identifying the rattan taboo defects because in this approach tracking starts from the destination, then find a rule that has the purpose for the conclusion. Furthermore, the tracking process uses the premise of the rule as a new goal and looks for other rules with new goals as the conclusion and the process continues until all possibilities are found. Backward Chaining is used to retreat from the destination to the path that leads to the destination. Therefore, it can be referred to as a driven goal. This research aims to make it easier for people to identify the defects of taboos and taboos, with the help of the application to provide knowledge about the defects in rattan taboos.